STRATEGIC DIRECTIONS OF MARKETING TECHNOLOGIES DEVELOPMENT IN THE CONDITIONS OF GLOBAL DIGITALIZATION OF ECONOMY - KOVALCHUK, SVITLANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The turbulent and innovative nature of development is demonstrated today by the digital economy, the basis for which is the formation of powerful technological changes in the creation of digital space for storage, processing and transmission of information. The pandemic caused by COVID-19 accelerated the global transition to the use of modern Internet technologies. Thus, according to the expert assessment of the United Nations Telecommunication Union (ITU), in 2021 the number of Internet users increased from 4.1 to 4.9 billion compared to 2019. In the first year of the pandemic alone, the number of people using the Internet increased by 10%, the largest annual increase in a decade. The same trends are characteristic of the Ukrainian market: in 2020 there were 2 million more Internet users in Ukraine, at the beginning of 2021 there were about 30 million. The number of Ukrainians who use social networks has increased significantly - 26 million people against 19 million in 2020. Users of the World Wide Web account for 60% of the total population, since 2020 their number has increased by 20%.The article summarizes the existing views on the definition of digital marketing, gives its author's definition as an effective combination of tools and methods of traditional marketing with modern information, digital, interactive technologies to promote goods and services, as well as building its business reputation in modern communication and information space. The tendencies in the field of digital marketing which have been formed, including under the influence of COVID-19, are defined, namely: tendencies of the advertising market; social network market trends; SEO market development trends; trends in automation and artificial intelligence. The landscape of digital marketing is defined. The main difficulties faced by digital marketing in 2021 are identified. The directions of further development of marketing in the context of global digitalization of the economy are outlined.
Keywords: marketing; marketing technologies; digital marketing; digital economy; globalization of the economy